The Handling and re-Management of The Product Failed in The Production Process of PT Kedawung Setia - Ahmad Ariq Rabbani; Zulfikar Steifani Prayoga; Pankkhurri Semwal (AIBPM Publisher, 2018)
PT Kedawung Setia Industrial Tbk manufactures and sells enamel products in Indonesia. Founded in 1973 and headquartered in Surabaya, Indonesia. PT Kedawung Setia main products are pot and household appliances lined with enamel. Enamel is a kind of special paint that makes the kitchen equipment become colorful so that is better seen and impress ‘luxury’. PT Kedawung Setia does not produce ordinary kitchen utensils, but rather a high-end kitchen appliances to be exported and able to be bought in large supermarkets. Thus it is certainly important for PT. Kedawung Setia to really pay attention to every detail of its production steps to minimize the occurrence of production failure. However the product defect seems to be quite difficult to avoid and still a problem that is putting a risk to the company. This paper aims to analyze the problem in production and display alternative solutions to reduce production failure which causes defect products. The result shows that it can be done via re-management of the defect product to be a new product with good quality adding up a diversification of products for the company